Role of endoscopic ultrasound in gallbladder and biliary system diseases in patients with normal transabdominal ultrasonography - Ahmed Morad Hashim; Ahmed Nabil Ahmed; Yasser Mahmoud Esmail; Abeer Awad; Yasmine Abd Elfatah (SpringerOpen, 2024)
Abstract Background The clinical management of patients experiencing recurrent abdominal pain resembling biliary-type, but with negative findings on conventional transabdominal ultrasound (TUS), poses a challenge. In recent years, endoscopic ultrasound (EUS) has emerged as a valuable tool for diagnosing gallbladder diseases. This study aims to assess the role of EUS in the evaluation of gallbladder and biliary system diseases specifically in patients with normal transabdominal ultrasonography results. Methods This study was a cross-sectional analytic study that enrolled 150 patients with any complaints related to the gallbladder and biliary system necessitating transabdominal ultrasound and endosonography in the period between February 2021 and December 2021. Results The mean age of the studied patients was 46.1 ± 10.3 years; 46.7% were males and 53.3% were females. The main complaint was right abdominal pain in 78.0%; meanwhile, 74.7% had a picture of obstructive jaundice. EUS revealed gallbladder wall thickening in 15 patients (10%), mud and/or small stones inside the gallbladder in 73 patients (48.7%), positive GB mass and/or polyp findings in 30 patients (20%), and biliary lesions such as duct strictures and/or dilatations were detected in 48 patients (32%), while transabdominal ultrasound was normal in all those patients. Conclusion Endoscopic ultrasound (EUS) proves to be a valuable diagnostic modality in patients experiencing biliary-type abdominal pain, despite normal transabdominal ultrasonography results. It not only aids in the accurate diagnosis of underlying conditions but also has the potential to impact the management plan for these patients.